El Niño‐Driven Dry Season Flushing Enhances Dissolved Organic Matter Export From a Subtropical Watershed. Issue 19 (8th October 2020) - Qu, Liyin; Wu, Yufang; Li, Yan; Stubbins, Aron; Dahlgren, Randy A.; Chen, Nengwang; Guo, Weidong
Abstract: The 2015/2016 super El Niño event resulted in a positive precipitation anomaly during dry seasons in the Jiulong River watershed, southeast China. Four years (2014–2017) of high frequency, in situ humic‐like fluorescent DOM (FDOMH ) data in the Jiulong Estuary were coupled with extrapolation to a freshwater end‐member FDOMH concentration and river discharge data to estimate riverine FDOMH export. The wetter El Niño dry season was followed by lower FDOMH export during the subsequent wet season. Furthermore, in the dry season after El Niño reached its strongest phase, a 90–187% increase in FDOMH export occurred. If widespread, this pattern suggests El Niño events may enhance export of FDOMH from south China rivers in dry seasons resulting in seasonal and annual shunting of the terrestrial DOM export, modulating coastal carbon cycling. This study highlights the need to incorporate climate‐driven regulation patterns on DOM transport across the land‐ocean interface. Key Points: 2015/2016 El Niño event induced a positive precipitation anomaly that increased FDOMH export during dry seasons from a subtropical watershed The wetter El Niño dry season was followed by lower FDOMH export during the subsequent wet season Watershed processes buffered FDOMH export relative to the El Niño‐induced increase of precipitation/discharge